How Reformist Islamic Theology Influences Muslim Women’s Movement: The Case of Liberal-Progressive Muslims in Indonesia - Nur Hidayah (Journal of Asian Social Science Research, 2020)
Reformist Muslim ideology has been perceived to liberate Muslim women from the shackles of patriarchal religious and cultural norms. This article analyzes the extent to which contemporary reformist Islamic theology influences Muslim women’s movement in the light of Muslim debates on women and gender issues. In doing so, it focuses on the case of Islamic reform by Indonesian liberal-progressive Muslims since the late New Order and its influence on the Muslim women’s movement in the country. This article argues that Islamic reform promoted by contemporary liberal-progressive Muslims has given a significant contribution to the development of Muslim women’s movement. It has laid the ground for an Islamic paradigm shift on the discourse on Islam and gender. The opening of the gate of ijtihad and respect for modernity espoused by reformist Muslims have provided tools for radical change in Islamic discourse on gender while still ground such change on an Islamic basis. It has empowered Muslim women to claim for the rights in religious knowledge production and build a critical mass of Muslim women who take an active part in the struggle for gender and social justice. However, the development of Muslim women’s movement has been far more vibrant through its engagement with the dynamic of its surrounding socio-political circumstances and though critical dialogue with broader currents of feminist thoughts. Such complex genealogies have enabled Muslim women’s movement to claim its own identity as indigenous Islamic feminism that poses multiple critiques to any unjust systems that deprive Muslim women of their rights.